Achieving balance between resident autonomy and patient safety: Analysis of resident-led microvascular reconstruction outcomes at a microsurgical training center with an established microsurgical training pathway. Issue 1 (January 2020) - Cho, Min-Jeong; Halani, Sameer H.; Davis, Justin; Zhang, Andrew Y.
Summary: Background: With advances in microsurgery, the published success rate of microsurgical reconstruction by experienced microsurgeons is greater than 95%. However, it is unknown whether the training residents can produce similar results. At our county hospital, residents perform and lead all aspects of microsurgical reconstruction, from raising the flap to performing microanastomoses. In this study, we retrospectively reviewed the outcomes of 156 consecutive microsurgical cases to determine the efficacy and safety of resident-led reconstructions at the county hospital. Methods: We performed a retrospective review of patients who underwent microsurgical reconstruction at the county hospital from 2016 to 2018. Demographic, surgical procedure, flap characteristics, resident levels, and complication data were collected. Results: Of the 156 free tissue flaps performed, the most commonly performed reconstruction was for the breast (62.8%), followed by lower extremity (15.9%), upper extremity (10.6%), head and neck (8.8%), and genitalia (1.8%). The average procedure time was 525.1 ± 149.2 min, and mean ischemia time for each flap was 69.8 ± 42.2 min. Venous anastomoses were performed by PGY3 (0.96%), PGY4 (27.9%), PGY5 (18.3%), and PGY6 (47.1%), while the arterial anastomoses were performed by PGY4 (16.4%), PGY5 (11.0%), and PGY6 (69.2%). The average number of anastomosis attempts was 1.3, with a range of 1 to 6. The overall flap success rate was 95.5% with a takeback rate of 7.1%. Conclusions: In conclusion, our analysis shows that resident-led reconstruction can achieve similar microsurgical success as that of published outcomes. We believe resident-led microsurgical reconstruction can be safely performed, with as-needed faculty assistance in high-risk and complicated cases, while allowing resident education and maturation of technical and decision-making skills.